Association of C-reactive protein-triglyceride glucose index with the incidence and mortality of cardiovascular disease: a retrospective cohort study - Yu Sun; Yu Guo; Shiyin Ma; Zhi Mao; Deguo Meng; Kaige Xuan; Ruogu Lu; Xudong Pan; Xiaoyan Zhu (Cardiovascular Diabetology)
Abstract Background The C-reactive protein-triglyceride-glucose index (CTI) has emerged as an innovative composite marker for evaluating metabolic-inflammatory dysregulation, integrating markers of insulin resistance and systemic inflammation. However, the association between CTI and cardiovascular disease (CVD) or its mortality has rarely been studied. This study sought to examine CTI's associations with CVD mortality, CVD incidence, and all-cause mortality. Methods This study included 8,679 adults from the National Health and Nutrition Examination Survey (NHANES) 2001–2010, 2015–2018. The CTI was derived as: 0.412* Ln (CRP [mg/L]) + Ln (TG [mg/dl] × FPG [mg/dl])/2, with participants categorized into quartiles. We employed Kaplan–Meier curves, cox proportional hazards model, logistic regression analyses, and restricted cubic spline (RCS) to evaluate CTI's associations with CVD mortality, total CVD incidence, and all-cause mortality across sex-stratified, age-specific, and glycemic subgroups. Results In this study, CTI was significantly and positively associated with CVD mortality, total CVD incidence, and all-cause mortality. CTI significantly predicted both CVD mortality (HR 2.28 [1.69–3.24]) and all-cause mortality (HR 2.14 [1.76–2.55]). Additionally, the CTI index correlated with the risk of total CVD (OR 2.85, 95% CI 2.32–3.52), congestive heart failure (OR 3.66, 95% CI 2.46–5.35), coronary heart disease (OR 2.82, 95% CI 1.95–3.97), angina pectoris (OR 2.85, 95% CI 1.89–4.22), heart attack (OR 2.59, 95% CI 1.89–3.52), and stroke (OR 2.86, 95% CI 2.00–3.85). Specifically, the association was similar between male and female, and similar in young participants and elderly participants. In different glycemic status, high levels of CTI were found to be linked to an increased risk of CVD in individuals without diabetes mellitus (DM). However, this association was not observed in individuals with DM. Conclusions Our analysis revealed that elevated CTI levels were significantly associated with CVD incidence and mortality. CTI may emerge as a unique predictive marker for CVD risk. Graphical abstract